0602 Rapid Eye Movement (REM) Sleep Duration Is Inversely Related To Daytime Pruritus Severity: Preliminary Findings in Posttraumatic Stress Disorder (PTSD) Patients. (25th May 2022) - Gupta, Madhulika; Gupta, Aditya
Abstract: Introduction: Pruritus (itching) is one of the most distressing symptoms of dermatologic disease. There can be a bidirectional relationship between pruritus severity and sleep. Pruritus during sleep is most frequently encountered during stages N1 and N2 and sleep fragmentation can exacerbate pruritus. Often there are limited effective treatments available for pruritus. In this study we examined REM sleep data obtained from PTSD patients who reported somatic complaints including daytime pruritus. To our knowledge there are no studies of REM sleep and pruritus during wakefulness. Methods: Seventy-five consenting patients with mild-to-moderate PTSD (all female; mean ±SD age 48.89 ±13.50 years) completed a battery of psychiatric and sleep ratings and underwent ≥ 1 home sleep apnea test (Watch PAT200; Itamar) which provided measures of %REM and REM duration. Exclusion criteria were use of benzodiazepines or narcotics. Pruritus was measured using Item 2 of the Pennebaker Inventory of Limbic Languidness (PILL), which assesses the frequency of common physical symptoms. For PILL Item 2 patients self-rated the frequency with which they experienced "Itchy eyes or skin" with a rating of "1" = ""never or almost never", "2"="less than 3 or 4 times per year", "3"="every month or so", "4"="every week or so', and"5"="more than once every week". Results: The mean±SD % REM was 21.78 ±7.64 (range 1.76% to 40.69%); and overall duration of REM sleep (mean ±SD) was 91.37±38.20 minutes (range 5.01 to 194.47 minutes). The frequency of pruritus ratings were as follows:: 39.5% endorsed a rating of "5" . The remainder self-endorsed the following frequencies: "4" (15.8%), "3" (21.1%), "2" (15.8%), and "1" (7.9%).. Pearson product moment correlation between the pruritus rating (item 2 of PILL) and REM sleep parameters were as follows: % REM (Pearson r= -0.172; p=0.144) and REM duration (Pearson r= -0.247; p=0.035). Conclusion: Daytime pruritus was inversely related to the duration of REM sleep in a sample of PTSD patients. Pruritus can be a difficult condition to manage. Optimization of REM sleep may have a role in the management of pruritus. Support (If Any): None